Pengelolaan Limbah Organik Kantin Menjadi Eco Enzyme Subtitusi Cairan Pembersih di PT. XX - Septiani, Riana; Sundari, Susanti (Yayasan Literasi Sains Indonesia, 2023)
The largest source of waste is generated from households at 38.3%. One of the methods of recycling organic waste by recycling is by fermentation, for example by producing eco-enzyme which is a solution of complex organic substances produced from the fermentation process of a mixture of organic waste, molasses and water. In this research, the purpose of using eco-enzyme is as a cleaning fluid for both sinks and crusty floors with the aim of seeing the effectiveness of eco-enzyme work with the aim of being a substitute for cleaning fluids sold on the market and including measuring the savings that can be made from this substitution in PT. XX, using experimental research methods. The results of research and observations show that eco-enzyme cleaning fluid is able to inhibit the growth of Escherichia coli (E.coli) bacteria as evidenced by a decrease in the number of bacteria (without eco-enzyme: 4.25 × 102 CFU/cm2; with eco-enzyme: 3.7 × 101 CFU/cm2) through swab tests and laboratory tests. Visual observations show significant results in making crusty floors clean. The savings that occur during 1 month by using eco-enzyme cleaning fluids as substitutes for cleaners sold in the market are IDR. 938,500/month.